Selected air pollutants and their effects on lung function among petrol station workers in Johor - Razak, Md Faizul Abd (2023)
Background: Petrol station workers are exposed to various air pollutants in their workplaces. These air pollutants include particulate matters (PM2.5 and PM10) and VOC that were proven hazardous to health, especially respiratory systems. With the increasing number of petrol stations, no enforcement on self-service, and no specific safety and health programmes, petrol station workers may develop abnormal lung function due to exposure to air pollutants. Objectives: This study aimed to assess the mean concentrations of air pollutants and their associations with respiratory illness among petrol station workers in Johor. Methodology: This cross-sectional study was conducted from January to December 2022 at selected petrol stations in Johor sampled using proportionate stratified random sampling. The concentrations of PM2.5, PM10, and TVOC at the petrol stations were measured. Subsequently, workers from the selected petrol stations were interviewed regarding respiratory symptoms using standardised questionnaires and underwent the lung function test. All data were analysed descriptively, and the One-way Repeated Measures ANOVA test was conducted to look for the mean differences in air pollutants concentrations. Logistic and linear regression analyses were used to identify associated factors of abnormal lung function and its parameters. Results: The mean concentrations of PM2.5 and PM10 at the petrol stations in Johor were 12.93 μg/m3 and 42.02 μg/m3, respectively, which did not exceed the 24-hour standard of WHO and NAAQS. There were significant mean differences in particulate matter concentrations between the different periods of the day [F (1.2, 52.6) = 95.587, p < 0.001 for PM2.5 and F (1.2, 53.3) = 158.294, p < 0.001 for PM10]. Mean differences in TVOC concentrations between various work processes or conditions were also found to be significant [F (1,43) = 3295.59, p < 0.001]. Ninety-three (38.3%) out of 243 petrol station workers had at least one respiratory symptom in which cough was the most commonly reported (25.9%). The prevalence of abnormal lung function among petrol station workers was 28.8%, predominantly obstructive impairment pattern (15.6%). Multiple logistic regression revealed that being a pump attendant (Adj. OR = 6.75; 95% CI: 2.70, 16.90; p < 0.001), duration of employment (Adj. OR = 1.05; 95% CI: 1.01, 1.08; p = 0.016), respiratory symptoms (Adj. OR = 13.44; 95% CI: 5.28, 34.23; p < 0.001), significant past medical history (Adj. OR = 20.77; 95% CI: 5.57, 77.45; p < 0.001) and workplace PM10 concentration (Adj. OR = 1.11; 95% CI: 1.06, 1.16; p < 0.001) were significantly associated with abnormal lung function. Conclusion: Abnormal lung function was quite prevalent among petrol station workers in Johor, even though the mean concentrations of air pollutants did not exceed the standard. This warranted more confirmatory studies to establish the causal relationship between air pollutants and abnormal lung function and the development of safety and health programmes for petrol station workers.